Measuring the Economic Growth and Community Welfare Through Analysis of Regional Revenue and Financial Performance - Garaika Garaika; Helisia Margahana; Sri Sarwo Sari; Winda Feriyana (Komunitas Dosen Indonesia, 2019)
The role of regional revenue in regional finance is one of the important benchmarks in the implementation of regional autonomy. This study aims to examine and give the empirical evidence of the direct and indirect effects of regional revenue and financial performance on economic growth and public welfare. The analytical method using the panel data analysis with fixed method to test the regression model. The finding reveal that regional revenue and economic performance on economic growth significant to the level of community welfare in the Regency/City of South Sumatra Province. The results of this study also prove that regional retribution is not significant to the welfare of the community. This study provides evidence that regional user fees are still unable to meet the budget targets so that regional user fees have a value that has not been able to improve welfare in the districts/ cities of South Sumatra province